X Space and the Revolution of Digital News Content: The Case of Generation-Z Protest Narratives in Kenya (African Multidisciplinary Journal of Research, 2025)
The power of digital media in Kenya has been demonstrated in the active social engagement and production of news discourse during the recent Generation-Z (Gen-Z) political activism on X Space. The discourse confirms a growing mass participation in news discourse on digital media taking precedence over legacy media. In the age of disruptive technologies, and the production of social-political discourses, an active, critical and content-producing mass is quickly surpassing traditionally assumed passive audience. In Kenya, amid a digital media frenzy over the Gen-Z protests, citizen journalism overrides legacy journalism, and in some cases, raw footage captured at points of witness is uploaded online without as much censorship. The paper applied qualitative in-depth interviews of eight journalists to assess the Gen-Z political activism and production of discourses on X Space. Theories of disruptive technologies were juxtaposed against the agenda-setting theory to identify the positive effects of digital narratives, including facilitating activism, active youth engagement in news discourse and social change. The study found out that a new form of youth activism has emerged, with the youth fruitfully engaging in X Space discourses, which culminate in actual street protests; Digital storytelling represents a powerful fusion of technology and social consciousness, where the young people project their voices of concern; Citizen journalism has fundamentally altered the dynamics of traditional journalism, reshaping the way news is gathered, reported, and consumed; and that during the protests, mainstream media played catch-up as it struggled to keep up with the many discourses emerging from X Spaces. The study recommends that traditional media aim to fully align with the opportunities presented in disruptive innovative developments; and that the Kenyan media grab the opportunity to re-evaluate their approach to gathering and disseminating news in the modern age for sustainable business and to maintain their important agenda-setting and gatekeeping roles.